(3MGTjI Ydi TQM GdJUQja GdYRj ddJaJGRGfjs - (3GdZRj, eMeO Hf bGSe Hf eMeO, J(B918(3g`s
(3ChdgG (B:s
(3jbhd eMeO Hf bGSe GdZRj GdTGaYjGdMeO ddg QH GdYGdejfhHYO agPG JYdjb dWja Ydi TQM GdJUQja jaJM ebadg hjTQM eTcdgs
(3BNQgG (B:s
(3bhdg(B: (3hYdjc HGdSeGY Cj GdSeGY deG LGA ef GdCHhGH GdKdGKI GdJj PcQgG haj ZjQgG cCHhGH cQGgjI hZdjJ hSQbI hjbGHI hRgGOI hOQGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 5s
(3eYLe GdeDdajf(B: 3 / 599s
(3cTa GdXfhf(B: 1 / 1140s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas